2022
DOI: 10.3390/su14063154
|View full text |Cite
|
Sign up to set email alerts
|

Do Corporate Social Responsibility Categories Distinctly Influence Innovation? A Resource-Based Theory Perspective

Abstract: Despite the existing vast literature on corporate social responsibility (CSR), there is a lack of research on the influences of CSR categories (i.e., employees; suppliers, customers, and consumers; environment; and social welfare). The objective of this paper is to investigate the influences of distinct CSR categories on firm innovation from a resource-based theory perspective. Based on a sample of Chinese A-share listed firms from 2010 to 2017, we find that employee-, supplier, customer, and consumer-, and en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 104 publications
(124 reference statements)
0
5
0
Order By: Relevance
“… Chen and Ji (2022) discovered that research results may only be confirmed during a period with a negative macro-political environment and fade during other eras. Therefore, it is essential to rule out this other explanation and re-evaluate our samples.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“… Chen and Ji (2022) discovered that research results may only be confirmed during a period with a negative macro-political environment and fade during other eras. Therefore, it is essential to rule out this other explanation and re-evaluate our samples.…”
Section: Resultsmentioning
confidence: 98%
“…The lower the price-to-book ratio, the greater the company’s investment value and growth prospects, and hence its emphasis on sustainable innovation. Several research has previously investigated and proven the inherent positive impact of CSR, innovation, and sustainable development ( Silvestre and Ţîrcă, 2019 ; Sharma et al, 2021 ; Chen and Ji, 2022 ; Liao et al, 2022 ). This study’s findings are consistent with past research in this area.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This theory highlights the role of demographic characteristics in managers' cognitive models. In addition, the upper echelons theory posits that senior executives are the key element in enterprise innovation decision-making [19]. Based on the upper echelons theory, the present study introduces the concept of executives' low-carbon awareness.…”
Section: Introductionmentioning
confidence: 98%
“…However, the relationship between them is still controversial at this stage, both in terms of theoretical explanations and empirical tests. Based on resource-based theory, some scholars believe that the resources available for discretionary use within a firm are limited and that implementing charitable giving and R&D innovation will lead to a "crowding-out" effect as they compete with each other in the firm's resource market [13][14][15][16]. Other scholars, based on stakeholder theory, believe that charitable giving helps firms to build a positive image [17], access external scarce resources [18], and build government-enterprise ties to mitigate the negative impact of policy uncertainty on R&D innovation [19], generating a "synergy" effect [20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%